Investigating customers' continuous trust towards mobile banking apps - Che, Maohao (2024)
Gaining continuous trust from mobile banking customers is a critical step in retaining customers for their usage of the provided services. The current study aims to investigate how customers’ continuous trust is formed at the continuous-use stage. Online survey responses from 450 frequent mobile banking users are collected. The data were analysed using structural equation modelling (SEM) based on a proposed model that predicts trust. The findings successfully validated the model and its reduced form. Based on the model, customers’ continuous trust can be predicted by mobile banking apps’ perceived ease of use, privacy assurance and security features, organisation reputation, customer support, and customers’ previous experience. Furthermore, the interactive relationships among these proposed factors are proposed and validated in the model. By studying trust in mobile banking past the initial adoption stage, we provide evidence to support the theoretical framework of investigating mobile banking continuous trust from the three constructs—mobile app (perceived ease of use, privacy assurance, security features), organisation (reputation, customer support), and customer (prior experience).